Supporting Dual CALP Development Among Second Language Learners: The Two-Way Model Revisited - Richard Gomez Jr.; Leo Gomez (Educational Considerations, 1999)
The most common bilingual education programs, early and late exit transitional bilingual models, are consistently undermined by external factors.